RATIONAL CHOICE ANALYSIS OF MICRO ENTREPRENEURS IN THE VICINITY OF BONTANG CITIMALL - Pipit Ade Nita; Agustin Nurmanina (Progress In Social Development, 2026)
This study aims to analyze entrepreneurial motivation and the changes in micro-enterprise conditions around Bontang Citimall, particularly after the shopping center began operating. The research employed a descriptive qualitative method, with data obtained through in-depth interviews with micro-business owners in Kelurahan Tanjung Laut. The findings indicate that entrepreneurial motivation is driven by economic needs, the desire for independence, and market opportunities arising from the high mobility of mall visitors. The presence of Bontang Citimall has had a significant impact on the economic aspects of micro-enterprises, including an increase in the number and diversity of consumers, higher sales turnover, and expanded business capacity. Although social changes are not visibly dominant, this study found changes in the interaction patterns among business actors, such as adjustments in operating hours and informal communication. Moreover, the study also reveals gaps in access to information regarding government MSME empowerment programs, including training, promotion, and financing schemes. These additional findings show the importance of synergy between modern infrastructure development and the strengthening of the local economy, as well as the improvement of MSME empowerment policy effectiveness to make it more inclusive.